Legal Protection Of Health Bpjs Accountability Regarding Hospital Refuse For BPJS Program Participants - Nuraeni, Yeni (SEAN Institute, 2023)
The government as a state implementing agency must strive for health insurance for every citizen, so that every citizen truly gets the right and protection to be healthy, as stipulated in Law Number 40 of 2004 concerning the National Social Security System. In fact, many residents complain about being rejected by the hospital when they are seeking treatment using BPJS services. The purpose of this study was to find out the reasons for the hospital's refusal of patients participating in the Social Security Administering Body (BPJS), and to find out the form of legal protection for BPJS Health's accountability regarding hospital refusal to the BPJS program participant community. The method used in this study is descriptive analytical with a normative juridical approach. The results of the study stated that there were cases of refusal from several hospitals to patients in terms of providing emergency services, this arrangement was explained in the RI Minister of Health. Number 1 of 2012 concerning the Individual Health Service Referral System. Rejection on purpose or in room mode has violated the MoU with BPJS as well as Law no. 24 of 2011 concerning BPJS. All patients must be accepted and served properly, no rejections. According to Law Number 24 of 2011 concerning BPJS, private and government hospitals are prohibited from turning away patients or asking for advance payments as regulated in Article 85 of the health Law. As for the suggestions that the author wants to convey, it is necessary to carry out more socialization to the community so that they can use BPJS Health properly. By taking into account the aspects of liquidity, solvency, prudence, security of funds, and adequate results and there should be strict sanctions for refusal of hospitals that are BPJS Health partners and addition of hospitals that are BPJS partners